Corynebacterium species in the female genital tract – pathogens or potential probiotics - IRINA V. GLADYSHEVA; SERGEY V. CHERKASOV (International Journal of Pharma and Bio Sciences, 2018)
The genus Corynebacterium contains more than 100 species, the vast majority of which have been isolated from human. The usual approach to consider this group of microorganisms alone as the causative agents of infection in humans has recently lost its relevance. The attention of researchers has been shifted to non-diphtheriae or non-pathogenic corynebacteria, whose major components are the normal flora of human skin and mucous membranes. In this review, we summarized the literature data and the results of our own research on the biological properties of the corynebacteria isolated from the female genital tract. We believe, that the non-diphtheriae corynebacterium present in the female genital tract has a high adaptive potential. Due to the unique biological properties, these microorganisms interact with the host organism and other representatives of the vaginal microbiota, which allow them to exist both in women with vaginal eubiosis and in women with nonspecific infectious diseases of the vagina. The ability of non-diphtheriae corynebacterium to produce organic acids, thereby reducing pH, stimulate the production of antiinflammatory cytokines, enhance the antagonistic activity of lactobacilli producing hydrogen peroxide against opportunistic microorganisms, as well as the ability to destroy biofilms of pathogenic microorganisms points to the important role of these microorganisms in the formation of eubiosis and, probably, determines the key role of non-diphtheriae corynebacteria in protecting the vaginal biotope from infection in those women who do not have lactobacilli. The data opens prospects for future fundamental medical research to study individual strains of non-diphtheriae corynebacterium as promising probiotic microorganisms.